Synthesis of multicarboxylic acid appended imidazolium ionic liquids and their application in palladium-catalyzed selective oxidation of styrene - Li, X; Geng, W; Zhou, J; Luo, W; Wang, F; Wang, L; Tsang, S (2007)
A series of multicarboxylic acid appended imidazolium ionic liquids (McaILs) with chloride [Cl]- or bromide [Br]- as anions have been synthesized and characterized. Deprotonation of these ionic acids gives the corresponding zwitterions. Re-protonation of the zwitterions with strong Brønsted acids gives a series of new ionic acid-adducts, many of which remained as room-temperature ionic liquids. A new catalytic system, McaIL/PdCl2 for the selective catalytic oxidation of styrene to acetophenone with hydrogen peroxide as an oxidant has been attempted. In the presence of McaILs, it is found that the quantity of palladium chloride PdCl2 used can be greatly reduced while the activity (TOF) and selectivity towards acetophenone are enhanced sharply. It is also shown that the catalytic properties of this system could be finely tuned through the molecular design of the McaILs. The best TOF value obtained so far is 146 h-1 with 100% conversion of styrene at 93% selectivity to acetophenone. In addition, the catalytic activity has been maintained for at least ten catalytic cycles. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.